2008
DOI: 10.1016/j.neuroimage.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and semantic context affect brain error-monitoring activity: An event-related brain potentials study

Abstract: During speech production, we continuously monitor what we say. In situations in which speech errors potentially have more severe consequences, e.g. during a public presentation, our verbal selfmonitoring system may pay special attention to prevent errors than in situations in which speech errors are more acceptable, such as a casual conversation. In an event-related potential study, we investigated whether or not motivation affected participants' performance using a picture naming task in a semantic blocking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
99
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 46 publications
(72 reference statements)
13
99
2
Order By: Relevance
“…Previous studies manipulating the amount of monetary loss for errors used only a single error type, although the amount of monetary loss was known before the error was committed. In these studies, monetary loss was manipulated between blocks of trials (Gehring et al, 1993;Ganushchak and Schiller, 2008) or was indicated by a cue or the stimulus (Hajcak et al, 2005;Potts, 2011). As a consequence, detection of an error was sufficient to update expected outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies manipulating the amount of monetary loss for errors used only a single error type, although the amount of monetary loss was known before the error was committed. In these studies, monetary loss was manipulated between blocks of trials (Gehring et al, 1993;Ganushchak and Schiller, 2008) or was indicated by a cue or the stimulus (Hajcak et al, 2005;Potts, 2011). As a consequence, detection of an error was sufficient to update expected outcome.…”
Section: Discussionmentioning
confidence: 99%
“…If updating expected outcome were based on an evaluation of error type, the Ne/ERN should be sensitive to the specific error type (i.e., larger Ne/ERNs should be obtained for errors associated with larger monetary loss). Although previous studies have shown that the Ne/ERN varies with the amount of monetary loss (Gehring et al, 1993;Hajcak et al, 2005;Ganushchak and Schiller, 2008;Potts, 2011), in none of these studies was an evaluation of error type necessary to update outcome expectations. Therefore, such a result would demonstrate that complex performance monitoring processes beyond mere error detection inform expected outcome computation already at a very early time point.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm entails a manipulation of the context in which identical object pictures are named. Behavioral studies have shown that naming latencies increase when objects are grouped or blocked into semantically related or homogeneous categories (e.g., chicken, whale, rabbit, giraffe, lamb) compared with noncategorized or heterogeneous groups or blocks (e.g., skirt, melon, tractor, cat, radish) (Ganushchak & Schiller, 2008;Belke, Meyer, & Damian, 2005;Maess, Friederici, Damian, Meyer, & Levelt, 2002;Vigliocco, Lauer, Damian, & Levelt, 2002;Damian, Vigliocco, & Levelt, 2001;Levelt et al, 1999;Kroll & Stewart, 1994). When naming objects in semantically homogeneous contexts, the self-monitoring system is presumed to be engaged to a greater degree than in heterogeneous contexts (e.g., to check whether the correct alternative has been chosen; see Ganushchak & Schiller, 2008;Maess et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was adopted because EEG is highly susceptible to mouth movements that could possibly mask the cognitive components of interest. However, at least one EEG study and several MEG studies have shown that artifact-free brain responses can be measured up to at least 400 ms after picture onset (10)(11)(12)(13), and a few recent ERP studies demonstrated that classical ERP components can be replicated during overt picture naming (14)(15)(16)(17).…”
mentioning
confidence: 99%